Longitudinal Effects of Mediums of Word Explanation on L2 Vocabulary Learning Strategies Among Chinese Grade-7 Students - Dong, Yang; Tang, Yi; Wu, Sammy Xiao-Ying; Dong, Wei-Yang; Li, Zhen (Frontiers in Psychology, 2020)
This longitudinal study investigated how different mediums of word explanation affected the use of English vocabulary strategies among Chinese Grade-7 students. 170 students were tested on their English receptive vocabulary size and vocabulary strategy application before and after an 8.33-month intervention. Students were divided into three experimental groups and one control group. The three experimental groups were provided with learning materials that explained the target vocabulary in three mediums, respectively: English-only, English-and-Chinese, and Chinese-only. Results showed that, after the intervention, receptive vocabulary size did not have any direct significant impact on vocabulary strategy development, whereas mediums of word explanation materials impacted students’ application of vocabulary learning strategies (VLS) in different ways. Our findings showed that the English-only mediums significantly enhanced students’ use of metacognition, cognition, and memorization strategies, but decreased social strategy development. Chinese-only mediums significantly facilitated cognition and memorization strategy development. Implications for L2 vocabulary education are discussed.